Método de modelagem domínio-ontológica do Direito Positivo Brasileiro - Roberto Figueiredo Paletta de Cerqueira (2007)
This interdisciplinary project considers a method for the construction of a legal domainontology model, directed to the brazilian positive Law, being applied into the modeling of the real estate conveyance tax of the City of Belo Horizonte, in OWL language, with the use of the Protégé ontology editor. The study reaches the theoretician-methodological beddings of the general and domain focused ontologies, the involved logical representation formalisms, and the critical analysis of the solutions presented in literature. The fundamental ontological commitment is based on the legal normativism of Hans Kelsen, making explicit in the model the concepts and values, and their existing relations, in the norms. The methodological strategy for the extraction of concepts is the content analysis. In the field of Right, the generic type of inquiry is the legal-description. The reasoning method for the construction of the ontology is hybrid. The presented final ontology is had to facilitate the interpretation of law.